2017
DOI: 10.1002/ange.201704959
|View full text |Cite
|
Sign up to set email alerts
|

The Viologen Cation Radical Pimer: A Case of Dispersion‐Driven Bonding

Abstract: The p bonds between organic radicals have generated excitement as an orthogonal interaction for designing self-assembling architectures in water.Asystematic investigation of the effect of the viologen cation radical structure on the strength and nature of the pimer bond is provided. As triking and unexpected feature of this p bond is that the bond strength is unchanged by substitution with electron-donating groups or withdrawing groups or with increased conjugation. Furthermore,t he interaction is undiminished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…After the first electron transition (stage "B"), a characteristic signal assigned to MV +• radical was observed, confirming the involvement of the MV 2+ → MV +• reaction. Near the end of the second charge plateau (stage "C"), an EPR signal with multiple peaks was observed, which implies the intermolecular interactions among the viologen units [54][55][56]. When discharging, the intensity of the multiple signal decreased (stage "D", with MV +• species dominant) and finally vanished at stage "E" (MV 2+ ).…”
Section: Resultsmentioning
confidence: 99%
“…After the first electron transition (stage "B"), a characteristic signal assigned to MV +• radical was observed, confirming the involvement of the MV 2+ → MV +• reaction. Near the end of the second charge plateau (stage "C"), an EPR signal with multiple peaks was observed, which implies the intermolecular interactions among the viologen units [54][55][56]. When discharging, the intensity of the multiple signal decreased (stage "D", with MV +• species dominant) and finally vanished at stage "E" (MV 2+ ).…”
Section: Resultsmentioning
confidence: 99%
“…While the two forms have not yet been distinctly detected in solution, DFT calculations show that the parallel and perpendicular forms of viologen radical cation dimers are similar in energy. Previously, the perpendicular form was predicted to be approximately 1.5 kcal/mol higher in energy than the parallel form . At room temperature, it is therefore expected that viologen dimers will rotate around their dihedral angle.…”
Section: Introductionmentioning
confidence: 97%
“…Solution phase viologens have been extensively characterized by UV–vis and resonance Raman spectroscopies , due to their blue color and by electron paramagnetic resonance (EPR) due to their radical nature. ,, The dimer has an absorption in the near-infrared and is EPR silent which makes it easily distinguishable from the monomer form. A recent study by Geraskina et al has identified by DFT that viologen dimers may exist as three rotamers in solution: parallel, perpendicular, and canted with intermolecular dihedral angles of approximately 0, 90, and 45°, respectively. The solid phase analogues of these structures have also been detected by X-ray crystallography and feature dihedral angles of ∼90, ∼0, or 33.5°. In the solid state, viologen radical cations do not technically form dimers but rather higher order aggregates of V •+ interacting with each other in various motifs and surrounded by counter-anions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5a ] In this regard, much effort has been devoted to exploring the sophisticated viologen‐based EC materials through post‐modification of viologens, polymeric viologens, and the construction of composites with inorganic materials. [ 5a,b,9 ] However, the practical use of the viologen‐based materials for ECDs is still hampered by their long switching time (>3 s), and low CE (<500 cm 2 C −1 ) due to the sluggish ionic diffusion and limited charge transport through the random and chaotic pathways during the switching process. A promising scheme to address these challenges relies on developing viologen‐based EC films with ordered channels for fast ion diffusion.…”
Section: Introductionmentioning
confidence: 99%